The Experiences of Australian School Mental Health Professionals during COVID-19 Lockdowns - Emily Berger; Grace Mackie; Andrea Reupert; Daliya Greenfeld; Kelly-Ann Allen; Fiona May; Gerald Wurf; Dianne Summers; Zoe Morris (MDPI AG, 2023)
Young people have emerged as one of the most impacted groups from the COVID-19 pandemic and related restrictions to daily activities, with disruptions to schooling, social interactions, and connections. Simultaneously, students' access to school mental health professionals were restricted or modified. The aim of this paper was to identify how school mental health professionals supported and addressed the mental health needs of young people during COVID-19 restrictions in Australia. School mental health professionals were surveyed during the 2020 lockdowns using a questionnaire designed by researchers in the United States of America. The innovations school mental health staff adopted to support students during lockdowns and remote learning were presented, including telehealth services, digital resources, and the online training and support they received/provided. The barriers and facilitators to providing counselling and assessment services during lockdowns were identified, including issues with providing psychometric assessments during remote learning, and ethical concerns when delivering remote counselling to students. Recommendations have been included, which address how school mental health professionals could be supported to assess and treat young people during future pandemics and school restrictions.